The Analysis of Potential Workplace Accidents Using Hazard Identification and Risk Assessment Method - -, Sarifaturrohmah; Wahyani, Widhy (Inscientech: Journal of Industrial, Science and Technology, 2017)
Abstract. Nowadays, in this globalization era, most of the companies develop machinery and tools supported by a sophisticated technology. They do believe that by using the technology, hope the process of production becomes faster than using pure man power. Moreover, the company can produce a huge number of products. However, on the other hands, sometimes an operator who works on a particular subject to an improper machine has skill. Therefore, it is able to cause the work accident which is in the several cases can be fatal. There was a company which has a textile business. It produced strings as an essential material for draperies and carpets. During the operators operate and the production machinery, an unexpected accident occurred. Often if it did not use the right or standard procedure. Refers to that background, the researcher does the analysis of the potential of workplace accidents in the spinning department by using the Hazard Identification and Risk Assessment Method. The results of the research that has conducted in that department was a potential of hazards commonly occur in that workplace are as follows: the workers fingers have pinched by the machine, the workers fingers have run over by the machine, unconscious, being injured in hands, and have the material downfall. As for, the hazard that has inflicted be included into the high level of risk, the which is: the workers fingers have pinched by the machine, the workers fingers have run over by the machine, unconscious, and being injured in hands. Furthermore the medium level of risk the which is: have the material downfall and lower level of risk which is: have a shock and legs injured. In addition, refers to the results of the research, the researcher could recommended several inputs to the company, exactly to the worker, the which is : keep fit, wearing a mask during do the job, arranging a space (safe distance) between the worker and the machine, wearing safety tools (safety gloves and shoes included), checking the condition before do the job, making sure that the fiber in the balanced position. Keywords: Hazard, Hazard Identification, Risk, Risk Assessment, Workplace Accidents, Potential Workplace Accidents.